Unsteady free convection in a porous open wavy cavity filled with a nanofluid using Buongiorno's mathematical model; International Communications in Heat and Mass Transfer; Vol. 67 - Sheremet M. A. Mikhail Aleksandrovich (2015, 2015)
Title screen